Case of angioimmunoblastic T-cell lymphoma presenting as peripheral and bone marrow plasmacytosis: A diagnostic conundrum - Deepika Gupta; Nagarjun S. Jaine; Sandeep K. Bairwa; Balamurugan Thirunavukkarasu; Vikarn Vishwajeet; Abhishek H. L. Purohit (Indian Journal of Pathology and Microbiology)
Angioimmunoblastic T-cell lymphoma (AITL), a subtype of peripheral T-cell lymphoma (PTCL), is associated with unique clinical, morphological, and immunohistochemical features. The peripheral circulation might show presence of an occasional reactive plasma cell but significant plasmacytosis masquerading as plasma cell leukemia is rare. We report a case of AITL in a 42-year-old male, who presented with two-month history of generalized lymphadenopathy. On investigations, he had hypergammaglobulinemia and plasmacytosis in the peripheral blood and bone marrow masquerading as plasma cell leukemia. Immunohistochemistry and serum protein electrophoresis revealed polyclonal nature of plasma cells. Diagnosis of AITL was made on cervical lymph node biopsy. This case highlights the diagnostic challenge faced due to heterogeneity in the clinical presentation and pathological findings and to alert the clinician so that timely accurate diagnosis can be made to initiate the treatment.